Prove that:
pls help me out..
Attachments:
![](https://hi-static.z-dn.net/files/d0e/57f0a23df2f8eeed373d84d031321b3a.jpg)
coolkriti692:
It is only matter of substituting the value ..try
Answers
Answered by
0
n(m^2-1) = 2m
LHS = secA+cosecA(sin^2A+cos^2A+2cosAsinA-1)
= secA+cosecA(1+2cosAsinA-1) (sin^2A + cos^2A = 1)
= secA+cosecA(2cosAsinA)
= 2sinA + 2 cosA
= 2(sinA+cosA)
RHS = 2m
= 2(sinA+cosA)
LHS = RHS
hence proved .
LHS = secA+cosecA(sin^2A+cos^2A+2cosAsinA-1)
= secA+cosecA(1+2cosAsinA-1) (sin^2A + cos^2A = 1)
= secA+cosecA(2cosAsinA)
= 2sinA + 2 cosA
= 2(sinA+cosA)
RHS = 2m
= 2(sinA+cosA)
LHS = RHS
hence proved .
Similar questions